Rencana Pelaksanaan Pembelajaran Menggunakan Technology Acceptance Model (TAM) - Solehuddin, M. (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
The advancement of information technology in the era of globalization has a significant impact on obtaining information, especially in the field of education. The right lesson plan must be made by educators as a supporter of success in advancing the education and learning process in schools.  This study aims to apply the Technology Acceptance Model (TAM) in analyzing the extent to which the information system developed can be accepted by users and influence user behavior in using the information system for assessing the quality of the lesson plan. This study uses TAM as an analytical framework to evaluate the level of acceptance of the system and produces output in the form of how high the level of acceptance of the information system created. This study uses the construct variables are convenience, usefulness, and acceptance of IT to be analyzed using SmartPLS. The results obtained show that the convenience variable and the usefulness variable have a positive effect on IT acceptance.